Evaluasi Waktu Tunggu Pelayanan Resep di Instalasi Farmasi RS Surya Insani Pasir Pangaraian - Sofina Lusia Harahap; Nur'aini Nur'aini; Arifah Devi Fitriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The implementation of pharmaceutical service standards in hospitals must be supported by the availability of pharmaceutical resources, organization oriented towards patient safety and standard operational procedures, where pharmaceutical resources include human resources as well as facilities and infrastructure. The purpose of this study was to determine the evaluation of prescription service waiting time at the Surya Insani Pasir Pangairan Hospital pharmacy. This study used qualitative research (In-depth interview) from this study the sample was 6 (six) people, namely 2 key informants, 2 main informants and 2 triangulation/additional informants totaling 6 people. The results of the study Human resources on prescription service waiting time at the Surya Insani Pasir Pangaraian Hospital Pharmacy Installation, Riau are still lacking. The required standard is 13 and the available is 9 so it requires 4 more people, facilities and infrastructure for waiting time for prescription services at the Pharmacy Installation of Surya Insani Hospital Pasir Pangaraian Riau meet 85% and there are still obstacles to speeding up services, the policy for waiting time for prescription services at the Pharmacy Installation of Surya Insani Hospital Pasir Pangaraian Riau is that SOP is enforced for 10 minutes for non-compounding and 20 minutes for compounding., supervision of waiting time for prescription services at the Pharmacy Installation of Surya Insani Hospital Pasir Pangaraian Riau is that SOP is enforced as a reference for work, there is training and education for waiting time for prescription services at the Pharmacy Installation of Surya Insani Hospital Pasir Pangaraian Riau., Suggestions are expected for hospitals As information for Surya Insani Hospital Pasir Pangairan so that they can intervene in order to make good Health Human Resource planning, As information material for Surya Insani Hospital Pasir Pangairan regarding things that are considered good or not considered good so that they can be an improvement in the future.